Arctic National Wildlife Refuge (ANWR): Legislative Actions Through the 108th Congress - Gillis, Anne; Baldwin, Pamela; Corn, M. Lynne; Gelb, Bernard A. (Library of Congress. Congressional Research Service., 2005)
This report provides a summary of legislative attempts from the 95th through the 108th Congresses, with emphasis on the 107th and 108th Congress, to address the issues of energy development and preservation in the Refuge.